The Comparison of Serum Zinc Level in Behcet Patients and Healthy Controls - Kamal Esalatmanesh (مجله دانشکده پزشکی اصفهان, 2009)
Background: Zinc was suggested as an antioxidant and immunomodulator trace element in parallel with other trace elements and antioxidant enzymes. Recently selenium deficiency was indicated in Behcet disease. In this study, we evaluated the correlation of serum zinc level and Behcet disease. Methods: In a cross-sectional, descriptive study serum level of zinc was measured in 49 cases satisfying International Study Group criteria and 51 controls. Serum zinc level was measured by atomic absorption spectrometry and compared the mean of Findings: serum selenium levels in both case and control and was analyzed by T-test statistical test. Serum zinc level (mean±SD) in patients (66.4±15.38) were significantly (p<0.0005) lower than healthy controls (86.87±17.18). When considering Global Physician Assessment, there was not significantly difference between active (67.47±14.3) and non-active (69.53±13.65) patients. A significant decrease in Zinc level was present in ocular involved patients. (p <0.001). Conclusion: Our results showed that serum zinc level is lower in patients than healthy control group. It is not clear that zinc is a predicting factor of exacerbation or activity of disease. More studies are needed for understanding the precise relationship between zinc and Behcet etiopathology. Key words:Behcet disease, zinc.